2015
DOI: 10.1111/ped.12583
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between umbilical cord hemoglobin and rate of jaundice requiring phototherapy in healthy newborns

Abstract: Higher cord hemoglobin may increase neonatal jaundice in newborns in Japan, therefore the present results support the Japan Resuscitation Council guideline 2010, which does not recommend delay of umbilical cord clamping by at least 1 min, in contrast to the ILCOR guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…The rates of cesarean section were comparable in the two groups (11/36 vs. 9/40, p = 0.426). The mean Apgar score did not differ among immediate and delayed cord clamping [9 vs. 9 , p = 0.783]. Birthweight was also similar [3210 (2720–4210) vs. 3370 (2640–3920), p = 0.280].…”
Section: Resultsmentioning
confidence: 99%
“…The rates of cesarean section were comparable in the two groups (11/36 vs. 9/40, p = 0.426). The mean Apgar score did not differ among immediate and delayed cord clamping [9 vs. 9 , p = 0.783]. Birthweight was also similar [3210 (2720–4210) vs. 3370 (2640–3920), p = 0.280].…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane review demonstrated significant increase of serum bilirubin in delayed cord clamping . For this reason, the Japan Resuscitation Council (JRC) guideline 2015 does not recommend delaying umbilical cord clamping by at least 1 min because Asian babies are, for reasons of race, more likely to develop jaundice requiring phototherapy …”
Section: Discussionmentioning
confidence: 99%
“…19 For this reason, the Japan Resuscitation Council (JRC) guideline 2015 does not recommend delaying umbilical cord clamping by at least 1 min 8 because Asian babies are, for reasons of race, more likely to develop jaundice requiring phototherapy. 20 It is unknown whether the blood volume and quantity of iron in the umbilical cord of an average newborn baby transferred in late cord clamping is sufficient to prevent the development of infant anemia. The blood volume transfused by milking 30 cm of umbilical cord in an extremely low birthweight infant is 18 mL/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between umbilical cord clamping time and various parameters such as postnatal and early infancy Hb levels, iron deficiency, iron deficiency anemia and risk of neonatal jaundice requiring phototherapy treatment has previously been studied 5,[8][9][10][11] , to the best of our knowledge, there have been no studies investigating the relationship between cord clamping time and the risk of significant hyperbilirubinemia by serial longitudinal TcB measurements, and early postnatal Hb and STB measurements. This study is the first in this field in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…and each 1 gram increase in cord Hb levels has increased phototherapy requirement by 1.7 times in a study conducted in healthy newborns. 5 Although there is only one study investigating the relationship between cord blood parameters (Hb level) and predicting the risk of later developing significant hyperbilirubinemia in the era of early discharge from the hospital, 5 there is, to our knowledge, no study investigating the relationship between the time of umbilical cord clamping and the risk of significant hyperbilirubinemia development especially with both serum total bilirubin (STB) and transcutaneous bilirubin (TcB) measurements. We, thus, aimed to investigate the relationship between the time of umbilical cord clamping and TcB measurements made on various postnatal hours, Hb and STB levels measured on postnatal 4th day, and the risk of development of significant hyperbilirubinemia requiring phototherapy treatment.…”
Section: Investigation Of the Relationship Between Cord Clamping Timementioning
confidence: 99%